Pengaruh Pengelolaan Arsip Dinamis Inaktif Terhadap Efisiensi Kerja Pegawai Di Dinas Perpustakaan Dan Kearsipan Kabupaten Padang Pariaman - Pratama, Yofri Firdiansyah; Erlianti, Gustina (Departemen Informasi Perpustakaan dan Kearasipan, 2023)
The background of this research is that archive management is not yet optimal, thus creating obstacles in retrieving archives because human resources do not have a background in archival science and employee work efficiency has not been optimally achieved. The purpose of this study was to determine the effect of inactive dynamic archive management on the work efficiency of employees at the Padang Pariaman District Library and Archives Service. This research approach is quantitative and causal-associative. The population in this study were employees of the Padang Pariaman Regency Library and Archives Service. The sample in this study was taken using a simple random sampling technique. Data was collected by distributing questionnaires. Data analysis techniques are used to see the description of the variables using the proportion formula and the mean (average). Meanwhile, to see the effect of variable X on variable Y using simple linear regression analysis, the results of this study indicate that: (1) management of dynamic archives is very well absorbed; (2) there is very good employee work efficiency; and (3) there is an influence of inactive dynamic archive management on the work efficiency of employees at the Padang Pariaman Regency Library and Archives Service. This can be seen from the results of the simple linear regression analysis, which obtained a significance value of 0,002 < 0.05.